Survival Outcome in Patients with Cardiomyopathy Detected by Gated SPECT Myocardial Perfusion Imaging - Sarker, Azmal Kabir; Nasreen, Faria; Nisa, Lutfun; Hussain, Raihan; Hoque, Harisul; Adhikary, Dipol K (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Quantitative assessment of LV dysfunction and viability through gated SPECT myocardial perfusion imaging (GSMPI) in addition to being diagnostic surrogate of cardiomyopathy (CM), are being increasingly reported as a predictor of adverse outcome in CM. This study was conducted to investigate the survival outcome in patients diagnosed with CM by GSMPI at National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Patients and methods: Patients who underwent Tc-99m Sestamibi GSMPI at NINMAS from January 2007 to December 2009 and were diagnosed with CM were retrospectively included in the study. The GSMPI parameters of diagnosis of CM were a left ventricular ejection fraction (EF) at rest of less than 40% with a corresponding end diastolic left ventricular volume (EDV) of more than 130 ml. Telephonic interviews of those patients were conducted in the year 2015 to obtain their clinical follow up data. Results: Fifty two patients (M/F=50/2) were diagnosed to have CM over a period of three years. Follow up data of 19 (M/F=18/1) patients with mean age 52.9±7.4 (38-65), EF 29.1±6.6 (18-39), EDV 211±45.4 (135-320) were available. Nine (47.4%) patients were alive at the time of follow up and 10 (52.6%) patients were found to be deceased. Thus, in this patient group one and five year survival was estimated to be 68 and 47%. Comparison of means of pretest probability score, GSMPI parameters of LV function and viability revealed no difference (p > 0.05) between survivors and non-survivors. Test of equality of survival distributions for management strategies revealed no difference either (Log Rank significance, p > 0.05). Conclusions: Five year survival in this study group diagnosed with CM by GSMPI was 47% where pretest probability score, GSMPI parameters and management strategies were not associated with difference of survival. Bangladesh J. Nuclear Med. 21(2): 81-86, July 2018